Pengembangan Bahan Ajar Matematika Berbasis Multimedia Interaktif Terhadap Prestasi Belajar Peserta Didik dalam Materi Fungsi - Subarkah, Muhamad Rizki; Raharjo, Hendri; Abdul Haqq, Arif; Mafatikah, Putri (Journal of Mathematics Learning Innovation, 2025)
This study aims to develop and assess the feasibility of interactive multimedia-based mathematics teaching materials as practical and effective learning media. The background of this study is the monotonous and one-way learning method without technology-based teaching materials in the school. The study used the Research and Development (R&D) method with the ADDIE (Analyze, Design, Development, Implementation, Evaluation) model. The subjects of the study were students of class X MIPA 3 at one of the high schools in Cirebon Regency. Data collection techniques included questionnaires, observations, tests, and documentation, with qualitative descriptive analysis for observation and quantitative analysis for validation of teaching materials. The results showed that interactive multimedia teaching materials had a feasibility level of 86.72% (very feasible) based on expert validation, and a practicality level of 96.70% (very practical) based on teacher and student assessments. In addition, this study showed an increase in student learning achievement after using the teaching materials. The implication of this study is that interactive multimedia-based teaching materials can be applied in mathematics learning to improve understanding of abstract concepts, such as functions. Educators and developers of learning materials are advised to consider integrating similar learning materials into learning and improving training for teachers in the application of learning technologies.